2010
DOI: 10.1111/j.1365-2788.2010.01353.x
|View full text |Cite
|
Sign up to set email alerts
|

Representation of people with intellectual disabilities in randomised controlled trials on antipsychotic treatment for behavioural problems

Abstract: Studies in which people with ID are included are of a sufficient quality, but of a small size. The heterogeneity in the characteristics of the ID population included as well as in the applied assessment instruments makes performing meta-analyses unfeasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 115 publications
0
13
0
Order By: Relevance
“…A recent review outlined that trials in this area generally involved too low numbers of patients with too much heterogeneity to draw conclusions (Scheifes et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…A recent review outlined that trials in this area generally involved too low numbers of patients with too much heterogeneity to draw conclusions (Scheifes et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…Among these prescriptions, those for antipsychotic drugs are the most frequent. Although some studies have shown that antipsychotics may be efficacious in treatments of challenging behaviours, the quality of these studies is generally poor (Deb et al., ; McQuire, Hassiotis, Harrison, & Pilling, ; Scheifes, Stolker, Egberts, Nijman, & Heerdink, ) and serious side effects frequently occur (Bhuvaneswar, Baldessarini, Harsh, & Aplert, ; De Kuijper, Mulder, Evenhuis, Scholte, Visser, & Hoekstra, ; Matson & Mahan, ). Some studies have shown that discontinuation of antipsychotics used for behavioural symptoms is possible without behavioural deterioration (Ahmed et al., ; De Kuijper, Evenhuis, Minderaa, & Hoekstra, ; Sheehan & Hassiotis, ).…”
Section: Introductionmentioning
confidence: 99%
“…The cases illustrate the use of psychotropic drugs from multiple therapeutic classes for the treatment of complex cases of mood dysregulation in ID. Despite being underrepresented in controlled clinical trials of psychotropic drug use for behavioral problems, 52 substantial percentages of adults with ID are reported to receive treatment with psychotropic drugs, particularly combination therapy regimens. In a study of 4069 community-dwelling adults with ID in New York State, 58% were receiving treatment with at least 1 psychotropic medication.…”
Section: Risk/benefit Considerations In Drug Treatment Selectionmentioning
confidence: 99%